KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH KOMPETENSI SDM DAN SISTEM PENGENDALIAN INTERN PADA KUALITAS LAPORAN KEUANGAN - Siwambudi, I Gusti Ngurah; Yasa, Gerianta Wirawan; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
The objectives of this study are to determine and obtain empirical evidence related organization commitment as moderated the effect of human resource competency and government intern controlling system at the quality of government financial report in the klungkung regency. This study was conducted on 37 work unit departments of Klungkung regency. Total number of respondent is 36 functionaries of financial department which was selected through purposive sampling technique. The analyzed data was primary data gained through survey and questionary technique. Then, data was analyzed by applying Moderated Regression Analysis method. The result of hipotesis testing shows that human resource competence have not effect on local government financial statement quality, however government intern controlling system do. Organization interaction commitment and both, human resource competence and government intern controlling system have not effect on local government financial statement  quality.
Keywords: human resource competence, government intern controlling system, organization commitment, financial statement quality